Integrated Reporting and Corporate Governance in the Digital Economy: Evidence from the Romanian Entrepreneurial Ecosystem - Clim (Moga), Loredana Maria (Acta Universitatis Danubius. Œconomica, 2025)
This paper aims to investigate how entrepreneurial ecosystems and innovation capabilities influence the adoption of integrated reporting and modern corporate governance practices among Romanian SMEs in the context of the digital economy. The study responds to an existing gap in understanding these dynamics in emerging economies. The research builds on existing models of entrepreneurial ecosystems, corporate governance and innovation in SMEs, extending them with empirical evidence from the Romanian entrepreneurial environment. A quantitative approach was used, based on a structured questionnaire addressed to Romanian SME managers, with the data analysed using structural equation modelling to analyse the relationships between ecosystem attributes, innovation levels, and financial performance. The results highlight that access to finance, entrepreneurial education and digital infrastructure significantly influence SMEs’ tendency to adopt integrated reporting. Innovation mediates the relationship between entrepreneurial ecosystems and financial performance, highlighting the importance of digital transformation. The conclusions provide practical directions for policymakers, SME managers and researchers, emphasising the need to strengthen entrepreneurial support mechanisms to promote transparency and organisational sustainability. The study makes an original contribution by highlighting the interdependencies between entrepreneurial ecosystems, innovation and integrated reporting practices, consolidating the specialised literature and offering practical applicability in emerging economies.